On being wronged and being wrong. (February 2017) - Slavny, Adam
If D commits a wrong against V, D typically incurs a corrective duty to V. But how should we respond if V has false beliefs about whether she is harmed by D's wrong? There are two types of cases we must consider: (1) those in which V is not harmed but she mistakenly believes that she is (2) those in which V is harmed but she mistakenly believes that she is not. I canvass three views: The Objective View, The Subjective View and The Mixed View . The Objective View holds that V's claim depends on the correct account of harm, rather than her false beliefs, and so D has a duty to offer damages to V in (2) but not in (1) in order to compensate her. The Subjective View holds that, for broadly anti-perfectionist reasons, V's claim depends on her sincere beliefs, even if they are mistaken, and so D has a duty to compensate V in (1) but not in (2). The Mixed View holds that we should defer to her beliefs in (1) but not in (2), so D has a duty to compensate her in both cases. In this article, I argue that we should accept The Mixed View .